Ammonia Induces a Myostatin-Mediated Atrophy in Mammalian Myotubes, but Induces Hypertrophy in Avian Myotubes - Stern, Rachel A.; Dasarathy, Srinivasan; Mozdziak, Paul E. (Frontiers in Sustainable Food Systems, 2019)
Ammonia, a byproduct of protein catabolism that is generally regarded as toxic, is processed by the liver for excretion. In diseases resulting in hepatic insufficiency, circulating ammonia levels increase dramatically, ensuing secondary disorders. Sarcopenia, or loss of muscle mass, is commonly associated with hyperammonemia. In mammalian models of cirrhosis, increased myostatin is consistent, contributes to muscle autophagy, and reduces satellite cell activation and differentiation, whereas, avian species show a positive myogenic response to ammonia. The objective of the study was to elucidate the effect of ammonia in chicken, mouse, and rat derived myotubes. Primary myoblasts were isolated from the pectoralis major (breast) and biceps femoris (thigh) of embryonic day 17 chicken embryos, and from the hindlimbs of 3-day-old rat pups. C2C12 cells were used for mouse myoblasts. Myotubes were exposed to 10mM ammonium acetate (AA) or 10mM sodium acetate (SA) for 24 hours to determine myogenic response to ammonia. Relative expression of myostatin mRNA, determined by quantitative real-time PCR, was significantly higher in mammalian myotubes compared to chicken myotubes (P < 0.001). Western blot analysis of myostatin protein confirmed a significant increase in ammonia treated rat myotubes, while chicken breast myotubes showed a significant decrease in myostatin (P < 0.05). Myotube diameter significantly increased in chicken breast and thigh cultures treated with ammonia, while diameter was significantly reduced in mouse and rat myotubes (P < 0.05). Intracellular glutamine is significantly higher in chicken thigh, but not breast, myotubes treated with AA compared to SA treated myotubes (P < 0.05). To investigate fiber type differences in ammonia metabolism, Western blot analysis of protein from AA and SA treated myotubes was examined for fast and slow myosin heavy chain isoforms. AA treatment resulted in a higher ratio of fast to slow isoforms of myosin heavy chain in both types of chicken myotubes, while fast isoforms were decreased in AA treated mouse and rat myotubes. These data demonstrate that chicken myotubes respond positively to ammonia while rodent myotubes respond negatively. Further, there is evidence that ammonia induces a fast fiber type shift in avian muscle, but a slow phenotype shift in mammalian muscle.